Duchenne Muscular Dystrophy: case report - Moraes, Fernanda Mendonça (2011)
Introduction: Duchenne muscular  dystrophy  is  a  hereditaryprogressive neuromuscular disease more common in the first twodecades of life and clinical manifestations are usually seen in thesecond year of life. It is an X-linked disease that affects mostly boysattending with muscular hypotonia and early muscle weakness.Diagnosis  is made  by molecular  biology  and measurement  ofCreatinoquinase and muscle biopsy and they should be done asearly as possible to allow the use of therapies that improve thequality of life.Objectives: To report a case of Duchenne muscular dystrophyand discuss clinical and diagnostic evaluation.Methods: Review of medical records and literature.Case report: Male patient, 11 year-old, born to non-consanguineousparents, with a negative family history for the disease. Since 18months he had frequent falls and walking at toes´ tips. With 5 yearsold it was observed difficulty to stand up and to use stairs. Due to theforward projection of the body he went to an Orthopedist and laterevaluations led to the suspicious of Duchenne Muscular Dystrophy.Physical examination showed hypertrophy of calves and GowersSign.  Laboratory  tests  showed: Creatine  kinase-total  6,334U/l(reference values= 26 to 189U/l); Lactate dehydrogenase of 2063U/l; Electroneuromyography showed a pattern consistent with muscleinjury.Conclusions: Despite being a known disease prognosis is lessinfluenced  by  the  use  of  therapies,  early  diagnosis  allows  theimplementation of techniques and medications that improve the qualityof life.